The role of gonadotropins and testosterone in the regulation of beta amyloid metabolism - Verdile, Giuseppe; Martins, R. (Cambridge University Press, 2009)
Regulation of testosterone and luteinizing hormone (LH) is tightly linked, and following reproductive senescence, sex hormone reductions are coupled with elevated gonadotropin levels. This chapter focuses on the sex hormone, testosterone, and the gonadotropin, LH. It outlines the role of these hormones in regulating beta-amyloid (Aβ) metabolism and amyloid precursor protein (APP) processing and discusses their potential as targets for developing effective therapeutic agents for Alzheimer's disease (AD). Sex steroid production is under the control of complex feedback loops within the hypothalamic-pituitary-ovary/ gonadal axis that regulate the levels of the pituitary gonadotropins, follicle stimulating hormone (FSH), and LH, in turn controlling estrogen and testosterone levels. The relative contributions of LH and testosterone to AD remain a challenge to be overcome by further experimentation. Given the diverse actions of the reproductive hormones, combinational hormone therapy may prove to be more efficacious in the prevention of AD.